Torsional Wave Propagation in a Pre-Strained Hollow Three-Layered Circular Cylinder - Akbarov, S. D.; Kepceler, T.; Egilmez, M. Mert (SPRINGER-VERLAG BERLIN, 2011)
This paper studies torsional wave dispersion in a pre-strained three-layered (sandwich) hollow cylinder made from high elastic materials the mechanical relations of which are described through the harmonic potential. The investigations are carried out within the scope of the piecewise homogeneous body model with the use of the three-dimensional linearized theory of elastic waves in initially stressed bodies. The analytical expression is obtained for the low wave number limit values of the torsional wave propagation velocity. The numerical results on the influence of the initial strains of the cylinders along the torsional wave propagation direction are presented and discussed.
Keywords: Initial strains; Wave dispersion; Three-layered hollow cylinder; High elastic material; Torsional wave; DISPERSION RELATIONS; Mechanics; Physics